The Defense Spending and GDP Nexus in the Middle East: Evidence from Gradual and Nonlinear Structural Shifts - Megoti , Madhuri; Oh, Dong-Yop; Lee, Hyejin (International Journal of Economics and Financial Issues, 2026)
This study examines the long-run relationship between defense spending and economic growth in 14 Middle Eastern countries from 1988 to 2023. Using Fourier LM unit root and Fourier ADL cointegration models, we account for gradual and nonlinear structural shifts often missed by conventional tests. Results show that most defense spending and GDP series are non-stationary but cointegrated once smooth breaks are incorporated. Income elasticity estimates reveal wide variation: oil-based economies such as Kuwait maintain rigid defense budgets, while the UAE and Lebanon show disproportionately higher responsiveness. Findings highlight how fiscal capacity and geopolitics shape defense and growth dynamics.